Marriage Apostates: Why Heterosexuals Seek Same-Sex Registered Partnerships - Palazzo, Nausica (Columbia Journal of Gender and Law, 2022)
Same-sex marriage is now a reality across Western countries. While this was a positive achievement for the LGBTQ community, some crucial questions remain unanswered. One of these questions concerns the future of nonmarital statuses, such as domestic partnerships or civil unions. After the legalization of same-sex marriage, U.S. states are simply phasing them out. I wish to argue against this trend. Based on an original analysis of empirical data and case law, I argue that nonmarital statuses retain value for non-traditional families. In fact, states must introduce nonmarital statuses open to couples regardless of gender, including adult friends and relatives. To support this argument, I present two analyses. First, I survey empirical research showing that (1) opposite-sex couples are signing up for nonmarital statuses at increasingly high rates, where available; (2) interest in such laws is growing even among same-sex couples in countries where same-sex marriage has existed for a long time. Second, I outline the legal and theoretical justifications for extending same-sex nonmarital partnerships to all couples. To this end, I analyze recent strategic litigation in Europe initiated by heterosexual couples who sought access to nonmarital statuses reserved for same-sex couples. The analysis allows me to identify three approaches: a status recognition approach, a utilitarian approach, and a legal-pluralistic approach. Ultimately, I offer guidance to policymakers in crafting a status that would be suitable for modern couples. Families that do not tick the boxes of the traditional marital family model continue to slip under the radar of law. Resurrecting these laws can fix the problem of their legal invisibility. Please note: minor changes have been made to this article on pages 213-14, and this pdf will differ slightly from hard copies or versions available elsewhere.